2014
DOI: 10.1149/2.0121501jss
|View full text |Cite
|
Sign up to set email alerts
|

Improved Plasma Resistance for Porous Low-k Dielectrics by Pore Stuffing Approach

Abstract: The pore stuffing method is studied with the objective of improving the plasma induced damage for porous organo-silicate glass low-k dielectrics. Experiments on blanket films show that, pore stuffing reduces the low-k degradation compared to non-protected porous films during plasma etch. The post etch surface roughness is also improved. The protection mechanism is attributed to reduced radical penetration, mainly fluorine and oxygen. The resistance against vacuum UV degradation is also improved by pore stuffin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
19
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 34 publications
1
19
0
Order By: Relevance
“…It was shown that the low‐k damage by VUV light cannot be completely avoided even when the pores completely filled with the sacrificial polymer. Significant penetration of fluorine into low‐k film after P4 and cryo processing has also been observed . Although in both cases the fluorine penetration itself did not change electrical characteristics of low‐k film, simultaneous effects of VUV light and fluorine atoms have not been studied in detail.…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that the low‐k damage by VUV light cannot be completely avoided even when the pores completely filled with the sacrificial polymer. Significant penetration of fluorine into low‐k film after P4 and cryo processing has also been observed . Although in both cases the fluorine penetration itself did not change electrical characteristics of low‐k film, simultaneous effects of VUV light and fluorine atoms have not been studied in detail.…”
Section: Introductionmentioning
confidence: 99%
“…This protective effect depends on both the polymer nature and level of porosity fill . This process is called post porosity plasma protection (P4) technology or the pore stuffing method . The protection mechanism is attributed to reduced penetration of radicals, such as fluorine and oxygen and the resistance against VUV degradation because of a higher VUV absorption coefficient compared with that for a Si‐O‐based dielectric network .…”
Section: Process Optimizations and Improvementsmentioning
confidence: 99%
“…This process is called post porosity plasma protection (P4) technology or the pore stuffing method . The protection mechanism is attributed to reduced penetration of radicals, such as fluorine and oxygen and the resistance against VUV degradation because of a higher VUV absorption coefficient compared with that for a Si‐O‐based dielectric network . However, the pore stuffing protection (PMMA, molecular weight = 4000 g·mol −1 ) against oxidizing radicals and VUV photons was insufficient for porous low‐k (k = 2.05) materials and no barrier Ta diffusion appeared during barrier deposition by physical vapor deposition .…”
Section: Process Optimizations and Improvementsmentioning
confidence: 99%
“…This new class of materials, commonly known as organosilicate glasses (OSG) or porous organosilicate glasses (p-OSG), can be deposited by plasma enhanced chemical vapor deposition (PECVD) or spin-on technology. 8 Pore stuffing mitigates the plasma-induced damage of the low-k dielectric because it prevents the diffusion of active species into the bulk of the porous material. 2 Plasma etching and resist strip (ash) cause methyl depletion which leads to moisture adsorption and degradation of the dielectric properties.…”
Section: Introductionmentioning
confidence: 99%